Colorful flexible polymer tandem solar cells. Issue 31 (26th July 2017) - Luo, Bangwu; Jiang, Youyu; Mao, Lin; Meng, Wei; Jiang, Fangyuan; Xu, Yang; Zhou, Yinhua
Abstract : Colorful flexible polymer tandem organic solar cells have been demonstrated using a transparent conducting polymer PEDOT:PSS as the top electrode as well as an optical engineering layer. Abstract : Fabrication of efficient colorful flexible polymer tandem solar cells remains a challenge. In this work, we report the use of poly(3, 4-ethylenedioxythiophene):poly(styrene sulfonate) (PEDOT:PSS) as the top transparent electrode in tandem solar cells that in the meantime acts as an optical coating for light engineering. Modification of the thickness of the transfer-printed PEDOT:PSS allows tailoring the reflectance spectra and yields colorful polymer solar cells with easy processability. Compared to the strategies of adopting optical microcavities and photonic crystals, the use of PEDOT:PSS also offers the important advantage of excellent mechanical flexibility that enables the fabrication of flexible colorful solar cells. The fabricated colorful flexible polymer tandem solar cells with polymer electrodes display power conversion efficiency (PCE) values from 7.23% to 8.34% depending on the yielded color of the cells, which are among the highest values for reported colorful polymer solar cells.